REVIEW ON THE BIODEGRADABLE RESIN BONDED SAND CASTING - N. I. S, Hussein; N. I., Mohamed Sokri; M. N, Ayof, (Journal of Advanced Manufacturing Technology (JAMT), 2014)
Resin bonded sand casting is widely used for manufacturing automotive parts especially those made of Aluminium Alloys. In general, resin bonded sand casting use alkaline resin as binding agent. Typically, they are from non-biodegradable materials that have issues on reclamation and disposal of the sand as well as cause hazard to the environment.  Therefore, this became a motivation to propose a biodegradable resin as the binding for the resin bonded sand casting mould. Review of this study is reported in this article. From the review, biocure starch resin with water or methyl ester made from plants was selected as binder. Feasibility to make resin bonded sand mould out of this resin need to be established. Further, the sand and cast material should be characterized and analysed for their microstructural and mechanical properties. Indeed, the review has given insight to the gap of this field of knowledge and aid in the development of aim and objectives of the research.